(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Spontaneous abortion or miscarriage is the spontaneous end of a pregnancy at a stage where the embryo or fetus is incapable of surviving independently, generally defined in humans at prior to 20 weeks of gestation, but in our country before 28 weeks of gestation. Nearly 20% of all confirmed pregnancies end in abortion. The incidence of this type of abortion is very high during first trimester and decreases with increasing gestational age. Of many types of abortion, missed abortion occurs when the embryo or foetus has died, but a miscarriage has not yet occurred. The retention of a fetus known to be dead for >4 weeks. The cervix is closed and there is no or only slight bleeding. Ultrasound examination shows an empty gestational sac or an embryo/fetus without cardiac activity. Surgical evacuation is the most common method of treatment of missed abortion.It is considered to be safe but carries some risk of complications related to anaesthesia and of surgical complications such as uterine perforation, cervical trauma, intrauterine adhesions and infections. Expectant management and medical treatment are the two other ways of treatment of missed abortion. Based on a review of the published literature, a single dose of 800?g vaginal misoprostol may be offered as an effective, safe and acceptable alternative to the traditional surgical treatment for this indication in the first trimester. Alternatively, 800?g misoprostol can be administered sublingually. Treatment may be repeated twice with a 3-4 hour interval for maximum three doses can be given orally or sublingually. Where as, vaginally, dose can be repeated 6-8 hourly for three doses. For the rest, 12-28 weeks of missed abortion,400?g of misoprostol every 4 hours until expulsion. Majority of cases have the expulsion within 48 hours. After administration of misoprostol, hospitalization is not necessary and the time of expulsion varies considerably. Bleeding may last for more than 14 days with additional days of light bleeding or spotting. The woman should be advised to contact a provider in case of heavy bleeding or signs of infection. A follow up is recommended after 1 to 2 weeks. DOI: http://dx.doi.org/10.3329/bjog.v26i2.13787 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(2) : 92-99